2018
DOI: 10.1186/s40168-018-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and ecotypic adaption of Holcus lanatus (L.) to extremes of its soil pH range, investigated through transcriptome sequencing

Abstract: BackgroundPlants can adapt to edaphic stress, such as nutrient deficiency, toxicity and biotic challenges, by controlled transcriptomic responses, including microbiome interactions. Traditionally studied in model plant species with controlled microbiota inoculation treatments, molecular plant-microbiome interactions can be functionally investigated via RNA-Seq. Complex, natural plant-microbiome studies are limited, typically focusing on microbial rRNA and omitting functional microbiome investigations, presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 89 publications
(105 reference statements)
0
17
0
1
Order By: Relevance
“…Meng and colleagues [16] propose a new method to separate the transcriptome of each member of the holobiont using metatranscriptomic datasets, allowing to access for the first time the whole functional diversity associated with the host and its microbiota. Young and co-workers [17] also used metatranscriptomics to characterize the microbiota associated with the wild grass Holcus lanatus and its changes in relation with soil types. In particular, they detected shifts in arbuscular mycorrhizal fungal communities according to phosphorus availability in the soil.…”
Section: New Tools and Methods To Dissect Holobiont Componentsmentioning
confidence: 99%
“…Meng and colleagues [16] propose a new method to separate the transcriptome of each member of the holobiont using metatranscriptomic datasets, allowing to access for the first time the whole functional diversity associated with the host and its microbiota. Young and co-workers [17] also used metatranscriptomics to characterize the microbiota associated with the wild grass Holcus lanatus and its changes in relation with soil types. In particular, they detected shifts in arbuscular mycorrhizal fungal communities according to phosphorus availability in the soil.…”
Section: New Tools and Methods To Dissect Holobiont Componentsmentioning
confidence: 99%
“…However, Ascomycota, Proteobacteria, Actinobacteria, Chloro exi, and Firmicutes were the dominant phyla under both well-watered and drought conditions. The predominance of Ascomycota in arid and semi-arid regions was previously reported [27,28]. Dai et al [29] found that Actinobacteria, Proteobacteria, Saccharibacteria, Chloro exi, Acidobacteria, and Cyanobacteria were the predominant phyla in drought-treated and untreated peanut rhizosphere.…”
Section: Discussionmentioning
confidence: 77%
“…The attention to different environments goes hand‐in‐hand with increased interest in modeling evolutionary responses in relation to climate change and environmental stress (Nagano et al ., ; Plessis et al ., ; Fournier‐Level et al ., ; Watson‐Lazowski et al ., ). Because transcriptional reprogramming was the standard in examining plant defense responses, in the EEFG framework, the transcriptional implications of responses to biotic interactors are more rigorously being considered at the systems level in natural environments (Turner et al ., ; Liao et al ., ; Nobori et al ., ; Young et al ., ).…”
Section: From Lab To the Field: Plant Genomics And Systems Biology Imentioning
confidence: 97%